Border optics: surveillance cultures on the US-Mexico frontier - Fojas, Camilla (Critical cultural communication, 2021)
Introduction: Border óptica, or seeing like a state -- Borderveillant media -- Drone futures : alien vs predator -- Wild border : surveillant ecologies -- Imperial border optics -- Coda: Border futures : seeing and foreseeing.